Towards a finite-state network for Northern Sotho deverbative nouns: the morphotactic rules. - Kotzé, Petronella Maria (Southern African Linguistics & Applied Language Studies, 2005)
In order to build a lexical transducer which can alternately generate grammatical forms and analyse the constituent parts of grammatical forms, the linguist has to provide the computer specialist with all the grammar rules relevant to a specific word category. These grammar rules are then transformed into morphotactic and alternation rules which would enable the lexical transducer to perform the functions of analysis and generation. In this article, morphotactic rules which would enable a lexical transducer to analyse Northern Sotho deverbative nouns are formulated. Descriptions in three major Northern Sotho grammars are scrutinised and compared to deverbative nouns from the Comprehensive Northern Sotho Dictionary, in order to establish whether the information contained in these grammars is adequate for the purposes of the lexical transducer. In instances where the Northern Sotho grammars provide inadequate information, revised rules are proposed by the author.